Langfristige fiskalische Erträge künftiger Zuwanderung nach Deutschland - Holger Bonin (Wirtschaftsdienst, 2015)
Angesichts der stark steigenden Zuzüge hat in Deutschland wieder eine gesellschaftliche Debatte darüber begonnen, was die richtige Zuwanderungspolitik ist, welche Vor- und Nachteile für das Land mit Zuwanderung verbunden sind und ob Migranten die öffentlichen Haushalte belasten, weil eine Zuwanderung in die Sozialsysteme stattfindet. Vor diesem Hintergrund analysiert der Autor die langfristigen Erträge von Migration für verschiedene Szenarien künftiger Zuwanderung mit den Mitteln der Generationenbilanzierung. – – The paper employs generational accounting to assess the long-term fiscal impact of future immigration to Germany. Using micro data on age-specific government revenue and expenditure, it demonstrates that the intertemporal government budget, given current fiscal parameters and no migration, is heavily imbalanced due to demographic ageing. Immigration may reduce the burden of the necessary fiscal policy changes on the incumbent population, both via an added revenue effect and an added tax payer effect. However, fiscal relief requires that future migrants are on average at least medium-skilled and hence better qualified than the current population of foreign nationals in Germany. This calls for selective migration policies with a strong labour market focus.
Keywords: E62; E66; F22; 330; Einwanderung; Öffentliche Finanzen; Generationengerechtigkeit; Deutschland